Gendered textual paralanguage in Indonesian skincare brand discourse - Kennia Wikanditha; Paramita Widya Hapsari Wikanditha; Anita Rusjayanti Wikanditha (Englisia: Journal of Language, Education, and Humanities, 2026)
This study investigates the role of textual paralanguage (TPL) in constructing gendered meaning within Instagram captions produced by Indonesian skincare brands. In response to a paucity of research on how gendered communication is realized through written paralinguistic features in established digital discourse—particularly where emotional expression and identity construction are salient—this study integrates discourse analysis with a sociolinguistic framework of gender. Employing a qualitative discourse-analytic design complemented by descriptive analysis, the study examines a purposively selected corpus of sixty Instagram captions from six Indonesian skincare brands, evenly divided between those targeting female (n = 30) and male (n = 30) audiences. Each caption serves as a unit of discourse and is analyzed using Luangrath et al.’s (2017) typology of textual paralanguage, comprising voice qualities, interpersonal resonance, typographic symbolism, visual kinesics, and punctuation cues. Frequency mapping identifies dominant patterns, while interpretive analysis focuses on the functional role of these features in conveying gendered meaning within their discursive contexts. Findings indicate five principal categories of TPL, each exhibiting distinct gendered tendencies. Captions oriented toward female audiences tend to be more expressive and relationally oriented, whereas those targeting male audiences are characteristically more concise and restrained, mirroring prevailing Indonesian sociocultural norms of femininity and masculinity. Collectively, the results demonstrate that TPL serves not merely a decorative function but a constitutive role in meaning-making within digital discourse. By systematically linking gendered TPL patterns to local ideologies of gender, this study advances linguistic scholarship on how written paralinguistic cues instantiate culturally specific gender norms in online brand communication.